Liver Cirrhosis: A Seven Year Follow-Up - TS Paul Tran; S Victor Feinman; Barnet Berris (Canadian Journal of Gastroenterology)
The status of 121 patients who were found to have liver cirrhosis on liver biopsy in 1981 was assessed seven years later. The etiology of the cirrhosis was alcoholic in 52%, cryptogenic in 29.8%, hepatitis B-related in 9.1% and miscellaneous in 9.1%. In 1981, jaundice was present in 55 patients (45.8%), ascites in 52 (43%), gastrointestinal bleeding in 25 (20.7%) and encephalopathy in 10 (8.3%). During the following seven years an additional 20 patients developed ascites, 15 gastrointestinal bleeding, 32 encephalopathy and three hepatocellular carcinoma. The mortality race was 43.8% at five years and 53.7% at seven years. The principal cause of death was liver failure (40%), followed by nonliver causes (32.3%) and gastrointestinal bleeding (13.9%). One patient died of hepatocellular carcinoma. Patients who survived seven years had fewer complications when seen in 1981 than those who died during this period (P<0.025). It is concluded that, in Toronto, cirrhosis is often caused by ethanol abuse and hepatitis B infection; that it is associated with significant morbidity and mortality; and that the number of complications when the patient is first seen may be a useful indicator of prognosis. Since many cases of cirrhosis are preventable, the authors suggest that efforts directed towards prevention of cirrhosis may be more rewarding than those directed towards therapy.